Pengaruh Mmanajemen Perubahan dalam Kemajuan Suatu Organisasi - Nurhaida Simatupang; Chuzaimah Batubara (Universitas Muhammadiyah Enrekang, 2023)
Change is a process that cannot be avoided in an organization. Organizational change is the process of isolating from the current state to a future state to improve the organization. Management in an organization must support the change process so that the organization can move forward. The success or failure of an organization is strongly influenced by its progress. Organizational changes are not always well received because, for every change, there will be resistance. The existence of organizational change can be a threat to an organization's success; therefore, it is necessary to have good management so that an organization can progress.